Policy Design for COVID‐19: Worldwide Evidence on the Efficacies of Early Mask Mandates and Other Policy Interventions. (17th October 2021) - An, Brian Y.; Porcher, Simon; Tang, Shui‐Yan; Kim, Eunji Emily
Abstract: To understand the extent to which a policy instrument's early adoption is crucial in crisis management, we leverage unique worldwide data that record the daily evolution of policy mandate adoptions and COVID‐19 infection and mortality rates. The analysis shows that the mask mandate is consistently associated with lower infection rates in the short term, and its early adoption boosts the long‐term efficacy. By contrast, the other five policy instruments—domestic lockdowns, international travel bans, mass gathering bans, and restaurant and school closures—show weaker efficacy. Governments prepared for a public health crisis with stronger resilience or capacity and those with stronger collectivist cultures were quicker to adopt nationwide mask mandates. From a policy design perspective, policymakers must avoid overreacting with less effective instruments and underreacting with more effective ones during uncertain times, especially when interventions differ in efficacy and cost.